Exploring Pelvic Symptom Dynamics in Relation to the Menstrual Cycle: Implications for Clinical Assessment and Management. - Blanco-Diaz, María; Vielva Gómez, Ana; Legasa-Susperregui, Marina; Pérez Domínguez, Borja; Medrano-Sánchez, Esther M.; Díaz-Mohedo, Esther (MDPI, 2024)
Background: Pelvic floor dysfunctions (PFDs) encompass an array of conditions with discrepant classification systems, hampering accurate prevalence estimation. Despite potentially affecting up to 25% of women during their lifetime, many remain undiagnosed, underestimating the true extent. Objectives: This cross-sectional study aimed to examine the impacts of the menstrual cycle on PFDs and dysfunctions. Secondary objectives included investigating differences between athletic and nonathletic women. Methods: An online questionnaire examined the effects of the menstrual cycle (MC) on 477 women's pelvic symptoms (aged 16-63 years), stratified by athletic status. This ad hoc instrument built upon a validated screening tool for female athletes. Results: Most participants reported symptom fluctuations across menstrual phases, with many modifying or reducing exercise participation. A concerning number experienced daily undiagnosed pelvic floor symptoms, emphasizing needs for comprehensive medical evaluation. Conclusions: Exacerbated pelvic symptoms showed complex relationships with menstruation, highlighting the importance of considering the MC in customized clinical management approaches. Symptoms demonstrated differential links to menstruation, indicating needs for individualized evaluation and tailored treatment plans based on symptom profiles and hormonal interactions. Educating professionals and patients remains essential to enhancing awareness, detection, and therapeutic outcomes. Further controlled longitudinal research should elucidate intricate relationships between menstrual cycles and pelvic symptom variability.
Keywords: Ciclo menstrual; Suelo pélvico - Fisiopatología - Tratamiento; Pelvic floor; Underdiagnosis; Menstrual cycle